Evaluation of Accuracy of OPG in Determining Root Morphology of Lower Third Molar When Compared with Gross Examination - Khurshid Abubakir Kheder Khrwatany (Erbil Dental Journal)
Dentists widely use Orthopantomogram (OPG). The accuracy of this device in providing information on root number and morphology has been the point of concern for many years.